Fraud Detection: Work Pressure With Personality Auditor? - Meylisa Febriani Rohyana; Ronald Wangdra (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
The purpose of this study is to analyze and test empirical evidence regarding the influence of job pressure, auditor competence, and risk culture on fraud detection, as well as to test the role of auditor personality as a moderation variable that can weaken, strengthen, or reverse the direction of influence between independent variables and dependent variables. The phenomenon of the research problems studied includes external pressure on auditors, limited auditor competence, where there are still few BPK auditors who have forensic audit certification in dealing with more complex fraud (especially in the field of IT and forensic audit), and organizational culture that does not always support fraud detection efforts. This study aims to explore how these factors affect the auditor's ability to detect fraud, as well as how the auditor's personality can play an important role in improving or decreasing the effectiveness of such detection. This study uses a descriptive and causal approach with primary data. This study makes a new contribution by adding auditor personality variables using five personality types that refer to the Big Five Theory. The population studied was auditor at BPK RI Riau Islands Representative, and data collection was carried out through the distribution of questionnaires via Google Form. Hypothesis testing is carried out using the Smart PLS application. The results showed that work pressure did not have a significant effect on fraud detection. However, auditor competence, auditor personality, and risk culture have a significant influence on fraud detection. In addition, this study found that auditor personality plays a moderation variable that affects the relationship between job pressure and fraud detection. Research shows the importance of synergy between various parties in detecting and handling fraud. Therefore, the government can encourage closer collaboration between auditors and investigators to strengthen efforts to eradicate corruption, both through policies that support cooperation between institutions and provide space for further coordination between supervisory and law enforcement agencies.